Identification of Resistance Pattern in Different Strains of Bacteria causing Septicemia in Human at Lady Reading Hospital of Khyber Pakhtunkhwa - Asif Aziz, Muhammad Zahoor, Aamir Aziz, Muhammad Asghar, Junaid Ahmad, Gohar Islam, Naheed (Pakistan Journal of Medical & Health Sciences, 2022)
Septicemia is one of the most life threatening problems and a major cause of morbidity and mortality particularly in neonates and children. The current research was carried out on identification and antibiotics susceptibility pattern of pathogens responsible for septicemia. A total of 121 samples were collected from septicemia suspected infants admitted in lady Reading Hospital (LRH), Peshawar, Pakistan. Among 121 samples, 43 (35.53%) blood cultures were positive for septicemia. Out of 43 cases, 27 (62.79%) showed growth of gram positive while 16 (37.20%) for Gram negative bacteria. The most common Gram positive isolates were Staphylococcus aureus 19 (70.37%) and Enterococcus spp., 8 (29.62%). Among Gram negative isolates were Klebsiella pneumonia 6 (37.5%), followed by pseudomonas aeruginosa 4 (25%) Escherichia coli 4 (25%), Citrobacter freundii 1 (6.25%) and Serratia 1 (6.25%). Staphylococcus aureus isolates were resistant to ampicillin followed by doxycycline, cefoxitin, gentamycin, but were sensitive to linezolid. Enterococcus spo., were resistant to gentamycin, ampicillin but sensitive to linezolid. Enterococcus spp., were resistant to gentamycin, ampicillin but sensitive to doxycycline followed by teicoplanin and minocycline. The P. aeruginosa were resistant to ampicillin followed by teicoplanin and minocycline. The P. aeruginosa were resistant to ampicillin followed by minocycline, aztreonam but sensitive to cefepime, gentamycin. The K.pneumonia isolates were resistant to ampicillin followed by aztreonam, gentamycin, doxycycline, minocycline but sensitive to cefepime. The E.coli XI isolates were resistant to ampicillin and cefepime followed by aztreonam, doxycycline, minocycline but sensitive to gentamycin. In this research, resistant pattern of 43 isolates were identified out of which 24 (55.81%) were MDR, 12 (27.90%) were sensitive, 7 (16.27%) were XDR and luckily no PDR isolate was found. Keywords: Septicemia, Sepsis,Antibacterial resistance